Review of 'Urf towards The Ritualization of Marriage in Gunung Meriah, Aceh (Al-Qisthu: Jurnal Kajian Ilmu-Ilmu Hukum, 2021)
This study aims to analyze the series of marriage traditions in the Gunung Meriah community, Aceh, using the theory of 'urf. The series of traditions consist of ubengan, wearing sindur, kembar mayang, dulungan, lempar sirih, and bakar menyan, all of which are carried out after the ijab-qabul. This study uses a qualitative approach with ethnographic data collection. The results show that the people of Gunung Meriah maintain a series of traditions around marriage because they are considered good. However, by using the 'urf approach, it can be seen that some of the series of traditions are classified as 'urf sahihah or traditions that do not conflict with Islamic law, which consist of ubengan, pakai sindur, kembar mayang, and dulungan. Meanwhile, some other traditions have the potential to be classified as 'urf fasidah or traditions that are contrary to Islamic law, namely lempar sirih and bakar menyan. In the tradition of lempar sirih, if the betel is thrown away, then it is classified as a bad deed, while if the betel is taken, then it is considered good. In the tradition of bakar menyan, if it is intended to summon the spirits of ancestors, then it is forbidden, whereas if the intention is simply to smell, then it is not forbidden.